The spectrum of psychotic disorders neurobiology, etiology, and pathogenesis - Fujii, Daryl 1961-; Ahmed, Iqbal 1951- (Cambridge University Press, 2007)
The spectrum of psychotic disorders encompasses as many as 25 different etiologies, ranging from the primary psychoses through those secondary to medical conditions, drugs and medications, and sensory impairments. This 2007 book provides a one-stop, comprehensive review of these disorders and gives quick comparisons for diagnostic decision-making to help with difficult differential diagnoses. Every chapter is uniformly structured to show comparisons between each disorder of presentation, course, and underlying neuropathology. Evidence for each etiology is also rated, indicating the confidence level the reader can place in the current findings. The international team of authors also examines data supporting a unitary neurobiological model of psychosis and the hypothesis that psychosis is a neurobiological syndrome similar to aphasia or apraxia. This book represents a paradigm shift in understanding, classifying and diagnosing these disorders, providing directions for future research and treatment. It will be of great interest to psychiatrists and neuroscientists alike